If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 1)(x + -5) = 0 Reorder the terms: (1 + 4x)(x + -5) = 0 Reorder the terms: (1 + 4x)(-5 + x) = 0 Multiply (1 + 4x) * (-5 + x) (1(-5 + x) + 4x * (-5 + x)) = 0 ((-5 * 1 + x * 1) + 4x * (-5 + x)) = 0 ((-5 + 1x) + 4x * (-5 + x)) = 0 (-5 + 1x + (-5 * 4x + x * 4x)) = 0 (-5 + 1x + (-20x + 4x2)) = 0 Combine like terms: 1x + -20x = -19x (-5 + -19x + 4x2) = 0 Solving -5 + -19x + 4x2 = 0 Solving for variable 'x'. Factor a trinomial. (-1 + -4x)(5 + -1x) = 0Subproblem 1
Set the factor '(-1 + -4x)' equal to zero and attempt to solve: Simplifying -1 + -4x = 0 Solving -1 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -4x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -4x = 0 + 1 -4x = 0 + 1 Combine like terms: 0 + 1 = 1 -4x = 1 Divide each side by '-4'. x = -0.25 Simplifying x = -0.25Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {-0.25, 5}
| .4x+13.5*.6=10 | | 4x^3y^2+8xy-12x^3y=0 | | 121-6x=-55+5x | | 3x-9+2x-3=6x+12-8 | | x(4+5)=5(x-2) | | 3(x+1)+6=-12 | | 121-6x=-55+5 | | 12-2m+5=-5 | | ax+7y=8 | | 3(x+0.1)-4(x-0.5)=5.4 | | -2y-5=y+4 | | 3d-11-7d=5 | | 3(x+0.1)-4(x-0.5)=54 | | 5(m-2)=8(m-2) | | log[2](3x+6)=4 | | 5x(x+5)=0 | | y=(x^2-5)(x^2-x^3) | | x=7i | | 152=-3+5(1+6n) | | -148=3(4+4x)+8x | | (4x+2)-(3x-3)=8 | | -11=x-18 | | (17/30)/(3)=z | | (17/30)/(1/3)=z | | 0=-16t^2+128-256 | | 0=-16t^2+128t-192 | | 12-3x=5x-12 | | (9/10)-(1/3)=x | | 5.972*2.71828=389.40563584 | | 7x-8(x+1)-3=3(x+4)-4(x+1) | | 3x+7=9x+3 | | 3n-5=-21 |